2021
DOI: 10.1299/jtst.2021jtst0037
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of knocking detection accuracy by an ion-current sensor integrated in the ignition system

Abstract: Enhancement of knocking detection accuracy by an ion-current sensor integrated in the ignition systemAbstract Abnormal combustion such as pre-ignition and knocking is becoming one of the biggest problems in the latest gasoline engines that have a higher compression ratio and boosting for higher efficiency. An ion-current sensor integrated in an ignition system is used for accurately detecting knocking cycles. First, the problem for accurate knocking detection with an ion-current sensor was clarified in the tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Ion current has been used to obtain flame information and detect misfires (41)(42)(43) , and studies have shown that it can be used to obtain the combustion state even for compression ignition at lean conditions in HCCI (44)(45)(46) engines. In addition, the detection of abnormal combustion, knocking and pre-ignition (47)(48)(49)(50)(51) , and the possibility of detecting precursors to preignition (52,53) have also been reported. Kumano et al (52) investigated the characteristics of ignition precursor phenomena in gasoline engines with a high compression ratio by using an ion current sensor integrated into the spark ignition coil.…”
Section: Combustion Control Of Advanced Enginesmentioning
confidence: 99%
See 1 more Smart Citation
“…Ion current has been used to obtain flame information and detect misfires (41)(42)(43) , and studies have shown that it can be used to obtain the combustion state even for compression ignition at lean conditions in HCCI (44)(45)(46) engines. In addition, the detection of abnormal combustion, knocking and pre-ignition (47)(48)(49)(50)(51) , and the possibility of detecting precursors to preignition (52,53) have also been reported. Kumano et al (52) investigated the characteristics of ignition precursor phenomena in gasoline engines with a high compression ratio by using an ion current sensor integrated into the spark ignition coil.…”
Section: Combustion Control Of Advanced Enginesmentioning
confidence: 99%
“…In addition, the detection of abnormal combustion, knocking and pre-ignition (47)(48)(49)(50)(51) , and the possibility of detecting precursors to preignition (52,53) have also been reported. Kumano et al (52) investigated the characteristics of ignition precursor phenomena in gasoline engines with a high compression ratio by using an ion current sensor integrated into the spark ignition coil. They identified the feature values of the ion current signal that correlated with the ignition precursor phenomena.…”
Section: Combustion Control Of Advanced Enginesmentioning
confidence: 99%
“…Ion current sensors for integration in the ignition coil and dedicated spark plugs for ion-current sensing were investigated. [21][22][23][24][25] Doi et al 24 enhanced the durability and sensitivity of ion current sensing by modifying the initial dimensions of electrodes. Bogin et al 25 showed that increasing the surface area of the positive center electrode of a spark plug greatly improved the peak ion signal.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al 28 applied a wavelet transform and designed wavelets to detect knocking from the ion current waveform. In our previous study, 23 we proposed a normalization method of ion-current oscillation intensity regarding the thermal characteristics of the ion-current signal to enhance knocking-detection accuracy.…”
Section: Introductionmentioning
confidence: 99%